If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11x + 4 + 8x + -4 + 3x = o Reorder the terms: 4 + -4 + -11x + 8x + 3x = o Combine like terms: 4 + -4 = 0 0 + -11x + 8x + 3x = o -11x + 8x + 3x = o Combine like terms: -11x + 8x = -3x -3x + 3x = o Combine like terms: -3x + 3x = 0 0 = o Solving 0 = o Solving for variable 'o'. Move all terms containing o to the left, all other terms to the right. Add '-1o' to each side of the equation. 0 + -1o = o + -1o Remove the zero: -1o = o + -1o Combine like terms: o + -1o = 0 -1o = 0 Divide each side by '-1'. o = 0 Simplifying o = 0
| 5g+7g-4= | | 35x-7y=491 | | 2x+54=2(x+28) | | 4(2x+3)+8=2(X+3)+4 | | -2x-22=-54 | | x+x=270 | | 3(X-5)+25=3X+10 | | 0.5x=0.2+75 | | X+4(2)=3 | | R+r+r+r+r=0 | | cosx^2=1 | | 0.3333x+14=40 | | 4(y-3)+9-3y=0 | | 0=-5X+-2X | | k-7.6=10.35 | | 0.5x^2=4y | | 0.333x+14=40 | | 15x^5+3x^4-40x^3-8x^2-15x-3=0 | | a-25=15 | | C=b-bx-5 | | 18x+2y=34 | | -8+5(g+2)=0 | | 2+0.54t=50 | | -6(4y)-7+2(7y+4)= | | 8(x-6)-5=4(x-4) | | -2x+17=9 | | 98-0.54t=50 | | 0.5(4x-16)-(-6)=-12 | | f(4)=.33 | | 0=2cos(x)-x | | 5k-20=12 | | 8x^2=-19x-6 |